The Technology of Happiness: Philosophy, the Body, and Ghazālī's Kīmīyā-yi saʿādat. (18th March 2016) - Ames, Robert
Abstract : This article suggests a repositioning of philosophy's disciplinary boundaries in terms of the analyses of ancient Greek philosophy carried out late in the career of Michel Foucault, which, under the influence of Pierre Hadot's conception of philosophy as a way of life, set out to highlight "the care of the self" as the practical core of the Ancient philosophical enterprise. In light of this shift in disciplinary boundaries, the article seeks to deepen the ongoing reconsideration of Abū Hāmid Muhammad ibn Muhammad al-Ghazālī's position vis-à-vis philosophy by highlighting the role of the body and self-care in his ethical writing. Though recent scholarship has come to reject the notion that Ghazālī simply did away with philosophy in Islam, even the studies of his constructive incorporation of Avicennan thought have stopped short of highlighting bodily discipline as a central feature of spiritual exercise across these categories.